Kinetics of processes in air plasma discharges at atmospheric pressure in the transverse flow of gas - Chernyak, V.Ya.; Tsymbaliuk, O.M.; Levko, D.S.; Martysh, E.V.; Iukhymenko, V.V.; Kolomiets, O.V.; Khomijak, V.O.; Chernysh, D.O.; Fentisova, O.I. (Вопросы атомной науки и техники, 2019)
The paper is devoted to the consideration of some features of the kinetics of the formation of nitrogen oxides and the population of the vibrational levels of the basic electronic states of nitrogen and oxygen molecules in the plasma of dry and humid air of gas discharges in the transverse gas flows to the current channel of the discharge at atmospheric pressure. Робота присвячена розгляду деяких особливостей кінетики утворення оксидів азоту і заселення коливальних рівнів основних електронних станів молекул азоту і кисню в плазмі сухого і вологого повітря газових розрядів у потоках газу, поперечних струмовому каналу розряду, при атмосферному тиску. Істотні відмінності виявлені в кінетиці процесів у плазмі сухого і вологого повітря. Работа посвящена рассмотрению некоторых особенностей кинетики образования оксидов азота и заселения колебательных уровней основных электронных состояний молекул азота и кислорода в плазме сухого и влажного воздуха газовых разрядов в потоках газа, поперечных токовому каналу разряда, при атмосферном давлении. Существенные различия выявлены в кинетике процессов в плазме сухого и влажного воздуха.